Pedagogical Transformation of Qur'an-Hadith Learning Across Madrasah Levels - Abdul Hakim; Debibik Nabilatul Fauziyah; Oyoh Bariah; Mohd Sobri bin Ellias (Jurnal Tarbiyatuna, 2026)
Qur'an-Hadith learning in Indonesian madrasas continues to face pedagogical challenges, particularly due to the dominance of memorization-oriented instruction and the limited implementation of student-centered learning. This study aimed to examine the pedagogical transformation of Qur'an-Hadith learning across three levels of madrasah education (MI, MTs, and MA) by identifying instructional practices and the pedagogical challenges encountered by teachers. This study employed a qualitative multi-site comparative design involving 18 Qur'an-Hadith teachers from six madrasas. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed thematically using NVivo. The findings reveal a gradual pedagogical transformation across educational levels. Learning at the MI level remains predominantly memorization-based. At the MTs level, teachers increasingly adopt interactive and deep-learning approaches, whereas at the MA level, they emphasize contextual, student-centered learning supported by digital technology. Across all levels, the major challenges include students' varying levels of Qur'anic literacy, limited learning environments, and teachers' readiness to integrate technology into instruction. These findings indicate that Qur'an-Hadith pedagogy in madrasas is evolving from traditional teacher-centered practices toward more contextual and learner-centered approaches. This study contributes to contemporary Islamic education by providing comparative insights into pedagogical transformation that can inform curriculum development and teacher professional development in madrasas.